An Early Application of the Average Total Cost Concept - Scherer, F. M (Journal of Economic Literature, 2001)
E BEGAN to conceptualize average total cost functions during the early decades of the twentieth century. But a century before, a German music publishing firm calculated and used in its internal decision making output-dependent average cost estimates for two methods of printing sheet music. This note describes that early experience and juxtaposes against it the relatively late emergence of the ATC curve in the formal literature of economics.